Comparing Three Methods for Producing Carbon Dots from Mangosteen Peel - Sugiarti, Sri; Safitri, Idayu; Darmawan, Noviyan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Carbon dots are fluorescent nanoparticles that are around 10 nm in size. Carbon dots can be formed via pyrolysis, hydrothermal, and solvothermal procedures from raw materials such as mangosteen peels. Because it contains cyanidin and xanthone, which improve the intensity of carbon dot fluorescence, mangosteen peel waste can be utilized to make carbon dots. The presence of a urea passivation agent is expected to boost carbon dot luminescence intensity. The study aimed to develop carbon dots from mangosteen peel using three different methods: pyrolysis, hydrothermal, and solvothermal, and to assess their ability to produce luminous hues. Carbon dot yield was 21% by the solvothermal method, 5% by the hydrothermal method, and 2% by pyrolysis. All three methods produced blue carbon dot luminescence. The solvothermal method, hydrothermal procedure, and pyrolysis had the highest luminescence intensity. Adding urea as a passivation agent increased the luminescence of carbon dots. The solvothermal approach produced the highest carbon dot production and fluorescence intensity. The hydrothermal and solvothermal carbon dots made emissions at wavelengths of 413 nm and 454 nm, respectively, both corresponding to blue luminescence.